Uropodina mites with unusual chelicerae from Thailand (Acari: Mesostigmata) - Kontschán, Jenő (Zootaxa, 2011)
A new monotypic genus Editella thailandica gen. nov., sp. nov., is described on the basis of one female and two males collected in Thailand. The new genus is unusual among Uropodina by the presence of an internal sclerotised node associated with the levator tendon in large, strongly dentate chelicerae. Taxonomic notes on the genus Hutufeideria are presented and three new species are described (Hutufeideria thailandica sp. nov., Hutufeideria phuketensis sp. nov., Hutufeideria alata sp. nov.). The name of the Australian species Hutufeideria hirschmanni (Hiramatsu, 1978) is a homonym of Hutufeideria hirschmanni Hiramatsu, 1978, from New Guinean, hence Hutufeideria hirschmannoides nom. nov. is proposed as a replacement name for the Australian species.